Semicommutators and Zero Product of Block Toeplitz Operators with Harmonic Symbols. (18th September 2013) - Cui, Puyu; Lu, Yufeng; Shi, Yanyue
Abstract : We completely characterize the finite rank semicommutators, commutators, and zero product of block Toeplitz operators T F and T G with F, G ∈ h ∞ ⊗ M n × n on the vector valued Bergman space L a 2 ( 𝔻, ℂ n ) .